PENGARUH KUALITAS PRODUK, CITRA MEREK, HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA BEAT(Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis) - Karina Ananda Hakim, (2023)
"This study aims to determine the effect of product quality, brand image and price on purchasing decisions of Honda Beat motorcycles. The type of data in this study uses quantitative data. In this study, the data sources to be analyzed were primary data. The population in this study were students at the Jakarta Veterans National Development University. The sampling technique used in this study is based on a non-probability sampling method using a purposive sampling approach. This study involved 120 respondents who were students who owned motorcycles with the Honda Beat brand. The data collected in this study came from questionnaires which were distributed in the form of a Google form. The questionnaire in this study was assisted by a Likert scale measurement. The results showed that (1) product quality influences the decision to purchase a Honda Beat brand motorcycle for students of the Faculty of Economics and Business, (2) brand image influences the decision to purchase a Honda Beat brand motorcycle for students of the Faculty of Economics and Business, (3) price influences the decision to purchase a Honda Beat motorcycle for students of the Faculty of Economics and Business."